2002
DOI: 10.1001/jama.287.24.3230
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Antioxidant Nutrients and the Risk of Incident Alzheimer Disease in a Biracial Community Study

Abstract: GROWING BODY OF EVIDENCE suggests that oxidative processes may be involved in the etiology of Alzheimer disease (AD). 1 Accumulated damage to lipid membranes and DNA by oxygen free radicals and reactive oxygen species is thought to disrupt normal cell functioning and lead to neuronal death. 2 Antioxidant nutrients, including vitamin E, vitamin C, and beta carotene, are among the body's natural defense mechanisms against oxidative stress. The antioxidant nutrients have been shown through animal and laboratory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
379
4
9

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 597 publications
(397 citation statements)
references
References 37 publications
5
379
4
9
Order By: Relevance
“…(25,67,84) A number of studies have shown that vitamin E intake from food sources is associated with beneficial outcomes in heart disease, (23) colon cancer, (85) and Alzheimer's disease. (24) It is noteworthy that over 80% of fats and oils used in the US are comprised of soybean oil. (10) High consumption of soybean oil is associated with increased serum gamma-tocopherol levels.…”
Section: Discussionmentioning
confidence: 99%
“…(25,67,84) A number of studies have shown that vitamin E intake from food sources is associated with beneficial outcomes in heart disease, (23) colon cancer, (85) and Alzheimer's disease. (24) It is noteworthy that over 80% of fats and oils used in the US are comprised of soybean oil. (10) High consumption of soybean oil is associated with increased serum gamma-tocopherol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of antioxidant supplements have found no protective effect [22], or a significant protective effect only with vitamin C [2], or only when both vitamins E and C are taken together [6]. Regarding dietary intake, studies have found a protective effect with intake of vitamin E [4,5] or vitamin C [4], whereas others have not found an effect [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Data from a handful of cohort studies suggest that the risk of AD may be reduced in people with a high dietary or supplemental intake of antioxidants [2][3][4][5][6]. Furthermore, low serum levels of B vitamins [7] and hyperhomocysteinemia [8] (which can be caused by B-group vitamin deficiencies), have been associated with an increased risk of AD.…”
Section: Introductionmentioning
confidence: 99%
“…These include, but are not limited to, flavonoids (e.g., quercetin, morin, or baicalein), β-carotene, curcumin, zinc, folic acid, and selenium. Most of these showed little promise as an AD therapeutic on their own, but when combined together in formulations they improved cognitive function in transgenic AD mice and reduced oxidative stress [129,130].…”
Section: Oxidative Damage As a Therapeutic Targetmentioning
confidence: 99%